Challenges and perspectives of greenhouse gases emissions from municipal solid waste management in Angola - Caetano Maria; José Góis; Anabela Leit\~ao (Energy Reports, 2020)
Municipal solid waste (MSW) management contributes substantially to climate change. The greenhouse gases (GHG) emissions from waste collection and landfill activities have a significant contribution. The carbon footprint is an important environmental indicator to express GHG emissions. Nowadays in Luanda, the capital and largest city of Angola, more than 2 million tonnes per year of unselected MSW are sent to landfill. The aim of this work is to evaluate the carbon footprint related to MSW in Luanda. The methodologies used to quantify the carbon footprint were based on the guidelines of the IPCC and the GHG Protocol of greenhouse gases emissions associated with MSW anaerobic decomposition, from the daily operations of the landfill site. The results show that direct landfill emissions are the major contributions to GHG accounting.
Keywords: 330; Carbon footprint; Greenhouse gases; Landfill; Municipal solid waste